What Measures for What Politics? Gender-Based Violence Protection and the RDL Policy Gap for Women in Italy (2021-2024) - Gatti, Rosa; Vittoria, Armando (PARTECIPAZIONE E CONFLITTO, 2025)
All forms of gender-based violence (GBV), particularly intimate partner violence (IPV), have intensified with the onset of the pandemic, partly because of closures associated with Covid 19. The pandemic has brought into sharper focus the link between GBV/IPV and economic or livelihood deprivation, highlighting that shelters and helplines for women are necessary but insufficient. The picture is even bleaker for immigrant women. The Italian case is very interesting. The government's decision to adopt a measure to protect women victims of domestic violence, the Reddito di Libertà (RDL) policy, during the pandemic was undeniably innovative, even if a few years later it shows limitations. This article examines GBV from an intersectional perspective and attempts to assess the coverage capacity of the RDL policy among Italian and foreign women living in Italy who are victims of IPV. The findings highlight how the RDL policy seems to have been designed more to manage emergencies than to effectively address GBV. Highlighting the selectivity in the application of the policy, the article concludes by arguing that it is necessary to consider the structural intersectionality that GBV feeds on to plan a more effective and inclusive policy strategy.